2013
DOI: 10.1007/s11910-013-0413-9
|View full text |Cite
|
Sign up to set email alerts
|

Newly Characterized Forms of Neurodegeneration with Brain Iron Accumulation

Abstract: Neurodegeneration with brain iron accumulation (NBIA) comprises a group of brain iron deposition syndromes that lead to mixed extrapyramidal features and progressive dementia. Historically, many patients with clinical and radiologic features of NBIA have not had a clearly identifiable molecular cause. Recent discoveries have shown that mutations in C19orf12 or WDR45 can lead to NBIA. C19orf12 mutations are inherited in an autosomal recessive manner, and lead to a syndrome similar to that caused by mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…1,3,7,10,12,15 Here we have demonstrated that although hemizygous germline variants in males are not universally lethal as it was originally presumed, they can result in a more severe phenotype. The direct clinical comparison of the two siblings here described revealed a more significant neurodevelopmental compromise at all ages in the male proband compared with his sister.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…1,3,7,10,12,15 Here we have demonstrated that although hemizygous germline variants in males are not universally lethal as it was originally presumed, they can result in a more severe phenotype. The direct clinical comparison of the two siblings here described revealed a more significant neurodevelopmental compromise at all ages in the male proband compared with his sister.…”
Section: Discussionmentioning
confidence: 86%
“…Its clinical course is described as biphasic with an initial presentation during childhood, as spastic quadriplegia or static encephalopathy with early developmental delay with or without seizures, followed by dementia in adulthood and the development of parkinsonism and dystonia. 1,4,[7][8][9][10][11] Heterozygous variants in the WD repeat-containing protein 45 gene (WDR45, OMIM: 300526) located in Xp11.23 lead to decreased autophagic activity and the BPAN phenotype. 12 All well-described cases of BPAN in the literature have been sporadic with a clear female predominance supporting an X-linked dominant pattern of inheritance with proposed lethality in males with germline variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurodegeneration with brain iron accumulation (NBIA) characterizes a number of progressive neurological disorders with the hallmark of iron deposition on MRI in several brain regions, most consistently the globus pallidus . Most of these are genetically determined although some patients, particularly with neurological symptoms beginning in mid to late adult life, have sporadic disorders of uncertain origin.…”
Section: Applying the Recommendationsmentioning
confidence: 99%
“…Neurodegeneration with brain iron accumulation (NBIA) characterizes a number of progressive neurological disorders with the hallmark of iron deposition on MRI in several brain regions, most consistently the globus pallidus. 214 Most of these are genetically determined although some patients, particularly with neurological symptoms beginning in mid to late adult life, have sporadic disorders of uncertain origin. Movement disorders, particularly dystonia and parkinsonism, dominate the clinical manifestations, but other common features include spasticity, ataxia, cognitive and psychiatric disturbances, and oculomotor abnormalities, optic nerve, retinal, and peripheral nerve involvement.…”
Section: Neurodegeneration With Brain Iron Accumulationmentioning
confidence: 99%